Pancoast Tumors: Persistent Diagnostic Challenge. (31st August 2017) - Feneis, Jennifer; Stark, Paul
Abstract : Superior pulmonary sulcus tumors, also called Pancoast tumors, represent a rare subset of bronchogenic carcinoma and account for 5% of all primary lung cancers. They represent a diagnostic and therapeutic challenge due to their atypical clinical presentation, which often results in a delayed initial diagnosis and complicated anatomic relationship of the neoplasm with the surrounding structures. This article reviews the anatomy of the thoracic inlet and the clinical and imaging features of this unusual manifestation of bronchogenic carcinoma, including conventional radiographic features and the CT and MR characteristics. It also discusses the diagnostic algorithm, the therapy, and the prognosis of patients afflicted with a Pancoast tumor, emphasizing the contribution of imaging to the diagnostic and planning process.